2015
DOI: 10.1016/j.ypmed.2015.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Great Taste, Less Waste: A cluster-randomized trial using a communications campaign to improve the quality of foods brought from home to school by elementary school children

Abstract: Objective Great Taste, Less Waste (GTLW), a communications campaign, capitalized on the synergy between healthy eating and eco-friendly behaviors to motivate children to bring more fruits and vegetables and fewer sugar-sweetened beverages (SSBs) to school. Methods A cluster-randomized trial in Eastern Massachusetts elementary schools in 2011–2012 tested the hypothesis that GTLW would improve the quality of foods from home more than a nutrition-only campaign – Foods 2 Choose (F2C) – or control. Lunch and snac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 44 publications
1
41
3
Order By: Relevance
“…In seven of the one-group designs, the pre- and post-tests were administered to different samples 9395,99100,105, 107,126 . Nearly three-quarters of the interventions and policies (39; 71%) were implemented in schools or multiple settings including schools 46, 4955, 5764, 7072, 76, 80, 86–102, 104108, 110111, 114133 . Additional settings included home 6667,109,112113 (4; 7%), clinic 4748,56,65,6869,7375,7779 (7; 13%), and community-based organizations 8185,103 (5; 9%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In seven of the one-group designs, the pre- and post-tests were administered to different samples 9395,99100,105, 107,126 . Nearly three-quarters of the interventions and policies (39; 71%) were implemented in schools or multiple settings including schools 46, 4955, 5764, 7072, 76, 80, 86–102, 104108, 110111, 114133 . Additional settings included home 6667,109,112113 (4; 7%), clinic 4748,56,65,6869,7375,7779 (7; 13%), and community-based organizations 8185,103 (5; 9%).…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 15 (79%) were conducted in countries similar in economic development to the U.S. 46,4954, 5760,6264,7779,106,115124,127129,133 . Twenty-two reported using a behavioral theory during development (40%) 4654, 5761, 6468, 7779, 8283, 9698, 110, 114118, 121124, 127129, 133 . Finally, 21 (38%) reported focusing their programs or policies toward one or more at-risk groups: those of low socioeconomic status 54,108,120124,133 (5; 9%), racial and/or ethnic minorities 47 (1; 2%), those who are overweight or obese 55,65,68,7375,7779,109,112,113 (8; 15%), those living in rural areas 56,72,98 (3; 5%), or multiple at-risk groups 6667,81,8485 (4; 19%).…”
Section: Resultsmentioning
confidence: 99%
“…It must be noted, however, that although we identified a statistically significant association between high knowledge scores and healthier beverage consumption habits, the observed effects were small in magnitude and thus improvements in knowledge may not translate to clinically significant improvements in behaviour. Indeed, this may explain why education-only interventions to improve beverage consumption habits are often unsuccessful in the long term (26,28,(66)(67)(68)(69)(70)(71)(72)(73) . Further research is therefore needed to understand how to maximize the effect of education interventions in order to capitalize on the association between knowledge and behaviour.…”
Section: Implications For Policy and Practicementioning
confidence: 99%
“…A description of the included studies is shown in Table 1. Of the 10 included trials, three were conducted in the U.S., [3133] three in U.K., [21, 3436] two in Australia [37, 38], one in Mexico [39] and one in Israel [40]. Eight of the studies employed cluster randomised-controlled trial designs, [21, 31, 32, 34, 3740] and two were conducted using quasi-experimental designs [24, 35]…”
Section: Resultsmentioning
confidence: 99%